Microenvironmental and cell intrinsic factors governing human cDC2 differentiation and monocyte reprogramming - Lang, Magdalena; Krump, Corinna; Meshcheryakova, Anastasia; Tam-Amersdorfer, Carmen; Schwarzenberger, Elke; Passegger, Christina; Connolly, Sally; Mechtcheriakova, Diana; Strobl, Herbert (Frontiers in Immunology, 2023)
cDC2s occur abundantly in peripheral tissues and arise from circulating blood cDC2s. However, the factors governing cDC2 differentiation in tissues, especially under inflammatory conditions, remained poorly defined. We here found that psoriatic epidermal cDC2s express the efferocytosis receptor Axl and exhibit a bone morphogenetic protein (BMP) and p38MAPK signaling signature. BMP7, strongly expressed within the lesional psoriatic epidermis, cooperates with canonical TGF-1 signaling for inducing Axl + cDC2s from blood cDC2s in vitro. Moreover, downstream induced p38MAPK promotes Axl + cDC2s at the expense of Axl + CD207 + Langerhans cell differentiation from blood cDC2s. BMP7 supplementation allowed to model cDC2 generation and their further differentiation into LCs from CD34 + hematopoietic progenitor cells in defined serum-free medium. Additionally, p38MAPK promoted the generation of another cDC2 subset lacking Axl but expressing the non-classical NFkB transcription factor RelB in vitro. Such RelB + cDC2s occurred predominantly at dermal sites in the inflamed skin. Finally, we found that cDC2s can be induced to acquire high levels of the monocyte lineage identity factor kruppel-like-factor-4 KLF4 along with monocyte-derived DC and macrophage phenotypic characteristics in vitro. In conclusion, inflammatory and psoriatic epidermal signals instruct blood cDC2s to acquire phenotypic characteristics of several tissue-resident cell subsets.